Study on Cultural and Heritage Tourism: Adilabad District: Exploring the rich cultural heritage of Adilabad district (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Tourism is one of the world's largest and fastest growing industries. Travel has been closely linked up with the evolution and progress of humankind. ''Travel for pleasure transformed into tourism. Tourism has developed into a big industry in recent years, both at the national and international levels. The tourist industry provides many benefits to the concerned society. Tourism is an area, which promotes human understanding. It has become an important social phenomenon of the modern society entailing demand on various facilities and services including transport, accommodation , restaurants, entertainment facilities , shopping outlets and sites of tourist attraction and thereby activating a process of accelerated economic production and distribution. Starting from the pre-historic sites, the history of Adilabad district passed through the political phases of Aryas, Mouryas, Satavahanas, Ikshvakus, Pallavas, Vishnukundins, Rashtrakutas, Western Chalukyas, of Kalyani, Kakatiyas, Musnuri Nayaks, Padmanayaks, Bahmanis, Qutb Shahis, Mughals and Asaf Jahi rulers. Finally, it became a part of Andhra Pradesh with effect from 1st November, 1956 under the scheme of State Reorganization Commission. The legacy of thousands of years of history has not only left material traces such as historic monuments, but also a wealth of material culture, be its customers, folklore, folk arts, handicrafts, culinary specialities, music , dance, fairs and festivals of Hindus, Muslims and Christians, etc. These fulfill all the aspects of cultural tourism.